Autonomic Nervous System Recovery After Various Exercises in Highly Trained Athletes - Saclova, Lucie; Nemcova, Andrea; Sacl, Jiri; Ronzhina, Marina; Smisek, Radovan; Smital, Lukas; Vitek, Martin (Computing in cardiology, 2022)
Introduction: Heart rate variability (HRV) , expressed by the beat-to-beat variation in heart rate, offers a noninvasive indicator of autonomic nervous system (ANS) activity. Measurement of the ANS response is increasingly used to evaluate the effect of training load on the organism. Most authors compared only the impact of different types of running training sessions (TS) (low-intensity training (LIT), high-intensity interval training (HIIT )) , or separately plyometric TS on HRV In this study, HRV was used to clarify how different types of running TS and plyometric TS influence post-exercise ANS response. Methods: 12 highly trained runners participated in this study. Each subject completed three types of TS - LIT running, HIIT running and plyometric. 5 - min pre-exercise ECGs were recorded just before TS and 5-min postexercise ECGs were recorded 10 min after TS . Altogether 13 time-domain and frequency-domain HRV features were calculated. Finally, the changes between pre- and postexercise values of HR V features were computed. Results: From 13 tested features, 9 and 10 features were statistically significant for distinguishing between plyometrics and LIT and HIIT and LIT respectively. There are no statistically significant differences in HRV changes between plyometrics and HIIT. It could be assumed these two TS affect ANS similarly.